Study of morphocytochemical and immunophenotypic features of acute leukemia stem cells - Gluzman, D.F.; Nadgornaya, V.A.; Sklyarenko, L.M.; Zavelevych, M.P.; Koval, S.V.; Poludnenko, L.Yu.; Ivanovskaya, T.S. (Experimental Oncology, 2008)
The immunophenotypic profile of hematopoietic stem cells (HSC) and hematopoietic precursor cells as well as leukemic stem cells (LSC) has been extensively studied in several laboratories worldwide. The results of our studies suggest that the standard panel for classification of acute leukemias should be supplemented with several new markers allowing us to identify more precisely the different forms of the leukemias being of the closely related origin, for example AML M6b and AML M7. The common bipotent LSC in AML M7 of low grade and AML M6b may exist analogous to precursor cell common for megakaryocytopoiesis and erythropoiesis. We have also found the similarity between blast cells in pro-B-ALL [t (4;11), 11q23] and AML M5a [t (9;11), 11q23]. Such similarity of immunophenotype and cytogenetic abnormalities in blast cells in pro-B-ALL and AML M5a may be considered as hint explaining the cases of AML M5a as a recurrence of leukemia in children with originally diagnosed pro-B-ALL. Иммунофенотипический профиль стволовых лейкемических клеток (СЛК) интенсивно изучают в ряде лабораторий мира.
Результаты данного исследования подтверждают, что стандартная панель для классификации острых лейкозов (ОЛ) должна
быть дополнена рядом новых маркеров. Это позволяет более точно идентифицировать близкие по происхождению формы
ОЛ, например ОМЛ М6b и ОМЛ М7. Предполагается существование общей низкодифференцированной бипотентной ЛСК
при ОМЛ М7 и ОМЛ М6b, подобной нормальной общей клетке-предшественнице мегакариоцитопоэза и эритропоэза.
Установлено также сходство бластных клеток при про-В-ОЛЛ с перестройкой хромосомного участка 11q23 и транслокацией
(4;11) и бластных клеток при ОМЛ М5а c перестройкой того же хромосомного участка 11q23 и транслокацией (9;11).
Подобное сходство иммунофенотипа и цитогенетических аномалий при указанных 2 формах ОЛ объясняет появление
бластов с фенотипом ОМЛ М5а при рецидиве заболевания у детей, у которых ранее был диагностирован про-В-ОЛЛ.